La Odilea by Francisco Chofre: a subversive text - Robles Mohs, Ivonne (2018)
In Francisco Chofre’s novel, the onomastics, in the broadest sense of the word, that is of names in general, highlights the polyphonic, carnival or subversive sense of the text, as is manifested in the title itself La Odilea.